Epidemiologic features and burden of atopic dermatitis in adolescent and adult patients: A cross-sectional multicenter study (2021)
ABSTRACT: Background: Atopic dermatitis (AD) is considered as one of the most frequent chronic skin conditions. Previous AD epidemiologic studies have been mainly retrospective and/or have been performed through surveys instead of in-person visits. Epidemiological studies concerning AD in Latin American countries are scarce. Objective: To describe sociodemographic and clinical features and the economic burden of AD on children and adult patients in Colombia through in-person visits. Methods: This was a cross-sectional study of 212 patients that included sociodemographic and clinimetric data. The diagnostic criteria of Hanifin and Rajka was used and data relating to disease distribution, disease severity (through the BSA: Body surface area; EASI: Eczema Area and Severity Index; SCORAD: Scoring Atopic Dermatitis), Fitzpatrick's skin phototypes, personal and familiar history of allergic diseases, previous treatments, and personal history of comorbidities, was collected. Results: Patient age range was 12-76, and 52.8% were female. Disease distribution was mainly flexural (19.6%). Early age start, Denni-Morgan fold, and infections tendency were more frequent in adolescents compared to adults. Mean age of diagnosis was 12 years old, AD diagnosis was made mostly by a dermatologist, 48.1% (102 patients) reported alcohol consumption, and 59% of consumers were heavy drinkers. Comorbidities found were: chronic rhinitis (68.9%) food allergy (32.5%), allergic conjunctivitis (29.7%), and asthma (28.8%). Around 81% earned less than $896 US dollars and 59% invested 6-30% of their monthly budget yearly, and 40% had work or school absenteeism. Mean scores of BSA, EASI, and SCORAD involvement were 32.6, 13.7, and 42.4, respectively. Conclusions: This study adds well-supported data through an in-depth clinical and economical characterization of Colombian adolescents and adult patients with atopic dermatitis and shows its high impact and burden on patients and their families. It also contributes to understand the burden of AD in Latin America.